Diversity of Fish Species in the Pinang Dalam Lake, Buluh Cina Village, Siak Hulu Sub-Regency, Kampar Regency, Riau Province - Kurnia, Faddillah; Efizon, Deni; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the diversity of freshwater fishes in the Pinang Dalam Lake wasconducted from January to March 2014. Fish samples were captured 4 times, once in 2weeks. This research aims to understand diversity of fish species, species of economicfreshwater fishes and decorated freshwater fishes in that area. Fish was captured using gillnet, seine, scoop-net, fishhook, fish trap and line fishing. The fishes captured were thendescribe and identified based on Saanin (1984) and Kottelat (1993) and they werephotograped. Result shown that the fishes are belonged to 3 orders, 11 families, 23genuses and 28 species. The fish collected are Barbodes gonionotus, B. Schwanefeldi,Cyclocheilichthys apogon, Hampala bimaculata, H. macrolepidota, Labiobarbusocellatus, Osteochilus hasselti, Oxygaster anomarula Puntioplites waandersi, Puntiustetrazona, Rasbora cephalotaenia, Thynnichtys polylepis, Botia hymenophysa, Mystusnemurus, M. nigriceps, Kryotopterus apogon, K. limpok, Ompok hypophthalmus, Wallagoleerii, Pangasius polyuranodon, Pristolepis grootii, Helostoma temminckii, Osphronemusgoramy, Anabas testudineus, Belontia hasselti, Trichogaster leerii, T. trichopterus andChanna micropeltes. Water quality parameters were as follows: temperature 28-290C,depth 130-450 cm, transparency 31-76 cm, pH 5, Dissolved Oxygen 4,10-6,56 mg/L.Keywords: Freshwater Fish, Diversity, Pinang Dalam Lake